Design Proposal of a Smoker-Dryer for Chicken - Alphonse Sawalda Guidzavai; Ngasop Ndjiya; Jean Hilaire Tchami; Nicolas Njintang (European Scientific Journal, ESJ, 2024)
Chicken breeders, particularly those in Ngaoundéré-Cameroon, after 45 days of breeding find themselves confronted with the problem of wasting nutrients and resources. In most cases, they sell their chicken at low prices to avoid expenses. Faced with these difficulties, some of them use various methods to preserve their chicken after 45 days of breeding, including cold preservation, smoking, and drying. Cold preservation is the most widely used technique, but this technique is energy-intensive, without forgetting the untimely power cuts and the deterioration of the quality of the product. By getting closer to its stakeholders, we were able to identify their difficulties and why they use cold preservation more, and they also entrusted us with the characteristics of equipment that could meet their requirements. In this article, we present the results from functional analysis to 3D modeling through the search for solutions to resolve contradictions. It emerges from this study that the model designed guarantees food safety and user safety, retains all nutrients, is ergonomic, uses fewer resources, is fast, and is adaptable to any type and size of the smoking product. We produced the designed model capable of containing 12 chickens, and we carried out the experiments in order to validate the model.